Ross Procedure in the era of Handmade-Valved Conduits for Right Ventricular Outflow Tract Reconstruction in Children: Short-Term Surgical Outcomes - Dong, Wei; Chen, Dian; Jiang, Qi; Hu, Renjie; Qiu, Lisheng; Zhu, Hongbin; Zhang, Wen; Zhang, Haibo (Frontiers in Cardiovascular Medicine, 2022)
Objective: Ross procedure is considered as the “gold standard” for aortic valve replacement, but the conduits used for right ventricular outflow tract (RVOT) reconstruction, such as homografts and bovine jugular vein (BJV) conduits, are of limited availability in China. Handmade expanded polytetrafluoroethylene valved conduits (HVCs) have been used recently as the alternative for RVOT reconstruction, but their specific experience in Ross procedure is limited in the literature. Methods: This was a retrospective review of 27 children who underwent Ross procedure in our center from January 2018 to January 2022. Results: Mean age at surgery was 8.0 ± 3.8 years. During the study period, BJV conduits were used for RVOT reconstruction in 6 patients (22%), and HVCs were used in 21 patients (78%). Median conduit size was 20 mm (range, 16~24 mm), and mean conduit Z-score was +0.8 ± 0.9. Median time for cardiopulmonary bypass was 158 min (range, 109~275 min), and mean time for aortic crossclamping was 110 ± 21 min. There was no early mortality. During a median follow-up time of 1.4 years (range, 0.1~3.7 years), 3 patients (11%) with BJV conduits had peak conduit velocity of greater than 3.5 m/s; 3 patients (11%) with HVCs developed moderate conduit insufficiency; no patients had more than moderate conduit insufficiency. Three patients with BJV conduits had 5 reinterventions, and all received conduit replacement with HVCs. Conclusion: HVC is an appealing alternative to BJV conduit for RVOT construction for children undergoing Ross procedure, with excellent short-term outcomes.